Der langfristige Zusammenhang zwischen demographischen und budgetären Variablen - Volker Ulrich; Manfred Erbsland (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
The German population is aging. Since fewer children are born and simultaneously life expectancy rises, demographic changes will lead to a double aging process. The paper analyzes the effects of demographic changes on the public budget by applying a cointegration analysis to global budget variables. Our procedure, which covers the period between 1950 and 1990, adds to prevailing projections, emphasizing that low vital rates are not the problem but their development over time. The estimation results of several error-correction-models show, that in the long-run an increase in the old age dependency ratio and a decline in the reproduction rate will lead to higher public expenditures. As regards public revenues, the results are ambivalent. The change in the age structures results in higher tax revenues, while the decline of population has the opposite effect. Furthermore, we find empirical evidence that aging increases the debt ratio. Compared to these long-run effects, the short-run dynamics is only of minor importance. Significant parameter estimates can be found mainly in the model for the social security contribution rate. Simulating the development of this rate on basis of an error-correction-model for the next four decades shows, that aging will further increase the tax load ratio and financing pay-as-you-go-systems will become more difficult. Nevertheless, there are a number of instruments the government can take to absorb these negative effects and to limit the burden to future generations.
Keywords: C32; J11; H61; 330